On the evolution of Lehman's Laws. Issue 7 (15th November 2013) - Godfrey, Michael W.; German, Daniel M.
SUMMARY In this brief paper, we honor the contributions of the late Prof. Manny Lehman to the study of software evolution. We do so by means of a kind of evolutionary case study: First, we discuss his background in engineering and explore how this helped to shape his views on software systems and their development; next, we discuss the laws of software evolution that he postulated based on his industrial experiences; and finally, we examine how the nature of software systems and their development are undergoing radical change, and we consider what this means for future evolutionary studies of software. Copyright © 2013 John Wiley & Sons, Ltd.